ENHANCING COMMUNITY LEGAL LITERACY AS AN EFFORT TO OVERCOME THE WEAKNESSES OF THE CONSUMER PROTECTION SYSTEM IN GOODS PURCHASE TRANSACTIONS - Rizaldy Alpiansyah; Irfan Alkhotiri; Harsing (STAI Minhajul Haq, 2026)
This research is motivated by the influence of student morality on several factors, one of which is the personality competence of teachers, especially Islamic Religious Education (PAI) teachers. To improve teacher competence in schools, especially the performance of PAI teachers, it is not enough to simply deliver lessons face-to-face in class, but the personality competence of PAI teachers must be able to build discipline, student morals at school, and a sense of responsibility. This study aims to determine the relationship between the personality competence of PAI teachers with discipline, student morals at school, and student responsibility at SMA Negeri 1 Bandung City. This study departs from the framework of thinking that the personality competence of teachers, especially PAI teachers, greatly determines the attitudes and behavior of students as role models both in the school environment and the community. The method used is a quantitative descriptive associative method and survey, with 120 respondents selected using simple proportional and random sampling techniques. Data collection using Google Form instruments, then analyzed with simple correlation, partial correlation, and multiple regression. The results show that the personality competence of PAI teachers has a positive and significant influence (relationship) on student discipline, morals, and responsibility. Good Islamic Religious Education (PAI) teacher personality competencies can improve students' discipline, morals, and sense of responsibility at school, although their impact varies from school to school. External factors such as the social environment, school culture, and interactions between students also influence student behavior. Therefore, developing teacher competencies must be balanced with creating a supportive school environment to ensure optimal character development.